DOES GEOPOLITICAL RISK MATTER FOR ASEAN5 ECONOMIES? EVIDENCE ON CONVENTIONAL AND ISLAMIC COMPLIANT INDICES - Anwer, Zaheer; Ahmad, Fiaz (Journal of Islamic Monetary Economics and Finance, 2025)
We assess the interlinkage of geopolitical risk and returns of conventional and Shariah Compliant indices from five ASEAN economies for the period Jan 2019 – Mar 2023 using daily data. We assess this phenomenon through the lens of the Efficient Market Hypothesis (EMH) and Risk and Return Theory. The sampled indices belong to Morgan Stanely Capital International (MSCI) and Standard and Poor (S&P). We employ Quantile Regression and Wavelet Coherence approaches. The results reveal that geopolitical risk does not significantly affect ASEAN5 indices for both conventional and Shariah Compliant categories. Moreover, there is very little dynamic co-movement between geopolitical risk and sampled indices. Malaysia and Indonesia emerge as the countries exhibiting the least co-movement and offer safe haven properties against geopolitical risk. The findings carry important implications for investors and policymakers.